The optimization problems in the differential calculus of a variable - Báez Ureña, Neel Lobatchewski; Blanco Sánchez, Ramón; Heredia Soriano, Wendy (Transformación, 2024)
Objective: This paper aims at devising didactic guidelines to students in solving optimization problems for developing skills to solve them by examining the causes limiting students’ performance. Methods: The author rely on methods of theoretical and practical nature. The former type was used to characterize the state of art and to construct a theoretical framework, the latter to explore the causes of students’ error by examining test results and its correspondence to what is describe in the bibliography. Results: The authors find out that the main causes of students’ difficulties in solving optimization problems are misusage of mathematic language, limitations in working with functions and transferring semiotic disabilities. Likewise, solving optimization problem procedures are devised. Conclusions: Modeling the problem, making a proper use of mathematic language as a necessary resource, and employing mathematics assistant for induction and verification of results are recommendable procedures to help students to solve optimization problems.